216 Fix or Replace: Is Internal Fixation Still A Viable Option in The Elderly with Un-Displaced Intracapsular Femoral Neck Fractures?. (12th October 2021) - Morris, R; Krishna, A; Hamid, H; Chawda, M; Mumtaz, H
Abstract: Aim: The treatment of impacted or un-displaced femoral neck fractures in the elderly osteoporotic patient is still largely debated, with arthroplasty versus internal fixation two surgical options 1 . Our aim was to retrospectively review patients over the age of 80 with un-displaced intracapsular hip fractures who had undergone internal fixation and assess their rate of mortality and revision surgery. Method: We conducted a retrospective review of all patients with femoral neck fractures over a 4-year period between January 2015 to December 2018. We refined this to only patients over the age of 80 with un-displaced intracapsular femoral neck fractures fixed with cannulated screws. We noted their mental and mobility status, their follow-up attendance over 3 years, their mortality and rate of revision surgery. Results: There were a total of 1232 femoral neck fractures in a 4-year period. Of these, 37 were >80 with un-displaced intracapsular femoral neck fractures, with 23 fixed with cannulated screws and 14 with a Dynamic Hip Screw. Mean age – 85, M:F (1:4.75). All patients were either Garden Classification Type I or II. 4% had cognitive impairment. All patients were independently mobile. 83% were followed up for 3 years, with 1 patient (4%) undergoing revision surgery 3 years following cannulated screw fixation. The 30-day mortality rate was 5%. Conclusions: The treatment choice for un-displaced intracapsular femoral neck fractures in the elderly remains debateable. Our retrospective review shows that the rate of re-operation is low in patients who have undergone fixation with cannulated screws and so this remains a viable option.